Innovation In Mud Crab Aquaculture: Implementation Of A Modular Culture System Based On Controlled Water Flow (Crab Flow System) In Tapanuli Tengah Regency, North Sumatra - Muhamad Latiful Khobir; Kurniawan Fazri (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Mangrove crab (Scylla spp.) aquaculture has high economic potential, but its implementation in coastal areas such as Central Tapanuli Regency still faces challenges, including limited land, water quality fluctuations, and maintenance efficiency. This study aims to develop and test the effectiveness of the Crab Flow System (CFS), a modular crab culture system based on controlled water flow designed to improve crab growth and survival performance. The research was conducted from January to March 2025 at the Laboratory of the Matauli College of Fisheries and Marine Sciences, North Sumatra, using an experimental method with two treatments: (1) conventional culture and (2) culture using CFS, each with three replicates. Parameters observed included daily growth rate (SGR), survival, and water quality (temperature, pH, DO, ammonia). Results showed that the use of CFS resulted in 18.4% higher average daily growth and 92% survival rate, compared to the conventional system. Water quality in the CFS system was also more stable and within the optimal range for crab growth. In conclusion, the CFS system proved to be effective in increasing the efficiency and productivity of crab culture, and has the potential to be an innovative solution for the development of sustainable aquaculture in coastal areas.